2022
DOI: 10.3390/jcm11226630
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium after Reconstructive Surgery in the Head and Neck Region

Abstract: Postoperative delirium (POD) is an acute and serious complication following extended surgery. The aim of this study was to identify possible risk factors and scores associated with POD in patients undergoing reconstructive head and neck surgery. A collective of 225 patients was retrospectively evaluated after receiving reconstructive surgery in the head and neck region, between 2013 to 2018. The incidence of POD was examined with regards to distinct patient-specific clinical as well as perioperative parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of these 16 observational studies included, 1 was a case-control study, 14 were retrospective cohort studies, and 1 was a prospective cohort study. Of the 16 articles, 12 studies were conducted in Asia (7 in Japan [ 12 , 18 23 ], 3 in China [ 24 26 ], and 2 in South Korea [ 27 , 28 ]), while 3 studies were performed in the Germany [ 5 , 15 , 29 ] and the remaining 1 study was conducted in the United States [ 30 ]. The most common diagnostic method was the DSM-IV in 8 of 16 included studies [ 12 , 18 , 19 , 21 , 22 , 24 , 27 , 30 ], the DSM-V in 4 studies [ 5 , 15 , 20 , 29 ], the CAM in 2 studies [ 25 , 26 ], and the ICDSC [ 23 ] and Nu-DESC [ 29 ] in the remaining 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 16 observational studies included, 1 was a case-control study, 14 were retrospective cohort studies, and 1 was a prospective cohort study. Of the 16 articles, 12 studies were conducted in Asia (7 in Japan [ 12 , 18 23 ], 3 in China [ 24 26 ], and 2 in South Korea [ 27 , 28 ]), while 3 studies were performed in the Germany [ 5 , 15 , 29 ] and the remaining 1 study was conducted in the United States [ 30 ]. The most common diagnostic method was the DSM-IV in 8 of 16 included studies [ 12 , 18 , 19 , 21 , 22 , 24 , 27 , 30 ], the DSM-V in 4 studies [ 5 , 15 , 20 , 29 ], the CAM in 2 studies [ 25 , 26 ], and the ICDSC [ 23 ] and Nu-DESC [ 29 ] in the remaining 2 studies.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to patients undergoing head and neck cancer surgery, there may be different risk factors for POD. Risk factors for POD after head and neck cancer surgery were reported in the individual studies, but the results were inconsistent or even conflicting [ 12 , 15 ]. Additionally, in 2017, Zhu et al identified several potential risk factors for POD after head and neck cancer surgery using univariate analysis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter study by Gazda et al associated early tracheotomy with lower odds of postoperative delirium [41]. While age seems to be a prominent risk factor for delirium, elective tracheotomy shortens the hospitalization on intensive care unit and shortens ventilation times, which in turn reduces the risk for delirium [3,42].…”
Section: Discussionmentioning
confidence: 99%